1979
DOI: 10.1111/j.1476-5381.1979.tb17331.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modulators of Arachidonic Acid Metabolism on the Synthesis and Release of Slow‐reacting Substance of Anaphylaxis

Abstract: Slow‐reacting substance of anaphylaxis (SRS‐A) was released in the peritoneum of passively sensitized rats challenged with ovalbumin and from rat isolated peritoneal cells stimulated with calcium ionophore A23187. Both monocytes (macrophages) and mast cells appear to be involved in the synthesis and release of SRS‐A. The immunological release of SRS‐A in vivo is enhanced by indomethacin and inhibited by dexamethasone, mepacrine, 1‐phenyl‐3‐pyrazolidone (1‐P‐3‐P), and methylimidazole. SRS‐A release induced by A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1980
1980
1987
1987

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Assays were performed in the presence of mepyramine and indomethacin, in order to rule out the role of histamine and cyclo-oxygenase products respectively. Neither BW755c nor ETYA, at concentrations which block the lipoxygenases (Hitchcock, 1978;Burka & Flower, 1979;Orning & Hammarstrom, 1980;Armour et al, 1981;Piper & Temple, 1981;Pattersson et al, 1981) inhibited the effects of Paf-acether. Moreover, BW755c suppressed the generation of leukotriene-like (i.e., FPL 55712 -inhibitable) substances detected with the coupled strips, validating its use as an inhibitor of the formation of leukotrienes in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Assays were performed in the presence of mepyramine and indomethacin, in order to rule out the role of histamine and cyclo-oxygenase products respectively. Neither BW755c nor ETYA, at concentrations which block the lipoxygenases (Hitchcock, 1978;Burka & Flower, 1979;Orning & Hammarstrom, 1980;Armour et al, 1981;Piper & Temple, 1981;Pattersson et al, 1981) inhibited the effects of Paf-acether. Moreover, BW755c suppressed the generation of leukotriene-like (i.e., FPL 55712 -inhibitable) substances detected with the coupled strips, validating its use as an inhibitor of the formation of leukotrienes in our system.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the conclusion of the first group, that SRS-A is a cyclo-oxygenase metabolite, differs from that of the second group who concluded that SRS-A is a metabolite of the lipoxygenase pathway. We have recently shown the situation to be even more complicated (Burka & Flower, 1979), in that SRS-A generated in vivo is enhanced by indomethacin but blocked by phenidone, an inhibitor of both cyclo-oxygenase and lipoxygenase pathways (Blackwell & Flower, 1978).…”
Section: Physiochemical Data On Srs-amentioning
confidence: 99%
“…Crude rat SRS-A was generated either by antigen challenge in vivo (Orange, Valentine & Austen, 1968) or by the calcium ionophore technique in vitro (Bach & Brashler, 1974;Burka & Flower, 1979). When the material was not processed immediately, it was stored in buffer aqueous solutions at -20°C.…”
Section: Generation Of Crude Rat Srs-amentioning
confidence: 99%
“…It has been assumed that leukotriene biosynthesis is dependent on membrane events which activate phospholipase A2 such that free AA is made available to the metabolic enzymes (Burka & Flower, 1979). The initial membrane events such as calcium mobilization also appear to be necessary for activation of the lipoxygenase pathway (Borgeat & Samuelsson, 1979;Jakschik & Lee, 1980).…”
Section: Introductionmentioning
confidence: 99%